1990
DOI: 10.1073/pnas.87.22.9010
|View full text |Cite
|
Sign up to set email alerts
|

Advanced protein glycosylation induces transendothelial human monocyte chemotaxis and secretion of platelet-derived growth factor: role in vascular disease of diabetes and aging.

Abstract: Diabetes and aging are commonly accompanied by arterio-and atherosclerosis. Infiltration of the arterial subendothelial intima by macrophages/monocytes is an important early event preceding the development of atheromatous lesions; these macrophages are known to produce mitogenic factors in early atherosclerotic lesions. It has been previously shown that, over time, vascular matrix accumulates proteins nonenzymatically modified by advanced glycosylation end products (AGEs). In view of the fact that macrophages/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
145
1
5

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 341 publications
(155 citation statements)
references
References 24 publications
4
145
1
5
Order By: Relevance
“…It is possible that human SMCs are quite resistant to increased oxidative stress, which mediates the effects of AGE-RAGE interaction in endothelial cells and monocytes/macrophages [46]. Therefore, direct effects of AGEs and S100 peptides on endothelial cells [13,47] and/or monocytes/macrophages [48,49] might be more pronounced than their effects on SMCs.…”
Section: Rage Ligands Do Not Stimulate Human Smc Proliferationmentioning
confidence: 99%
“…It is possible that human SMCs are quite resistant to increased oxidative stress, which mediates the effects of AGE-RAGE interaction in endothelial cells and monocytes/macrophages [46]. Therefore, direct effects of AGEs and S100 peptides on endothelial cells [13,47] and/or monocytes/macrophages [48,49] might be more pronounced than their effects on SMCs.…”
Section: Rage Ligands Do Not Stimulate Human Smc Proliferationmentioning
confidence: 99%
“…A syndrome of insulin resistance, central obesity, hypertension and dyslipidaemia, also known as the metabolic syndrome, may constitute these common precursors. Evidence from an increasing number of basic research studies points to a causal role of oxidative stress and inflammatory processes in the aetiology of type 2 diabetes and the metabolic syndrome [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in vitro have shown that AGE can mediate monocytic chemotactic activity [6], and block the cytostatic effect of nitric oxide-dependent vasodilatation [7]. AGE modification of mesangial cell matrix has been reported to alter the mesangial proliferative response [8].…”
mentioning
confidence: 99%